Finite Element Analysis (FEA) Study on Glass Fiber Reinforced Epoxy (GRE) Pipes Used in Oil and Gas Industry - Muhammad Faris, Muhammad Khairulanwar; Khirotdin, RD Khairilhijra'; Khirotdin, Rd Khairilhijra (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The requirement to describe and comprehend the engineering performance of GRE pipes becomes more crucial as applications spread, and a better understanding of the performance of glass fibre-reinforced epoxy (GRE) pipe also needs to be considered due to the improvement of this material for oil and gas industry pipes. Furthermore, GRE has been considered an alternative to carbon steel. Therefore, this research objective is to analyse the tensile strength, fatigue behaviour, and corrosion behaviour of the GRE and then to determine by comparing the analysis result of GRE with a carbon steel pipe. The research has been completed by conducting an analysis using ANSYS software to analyse tensile strength, fatigue behaviour and corrosion behaviour by using three different geometries which is minimum, medium, and maximum to see the outcomes differences for both GRE and carbon steel pipes. The outcome from the analysis shows the percentage of differences between GRE and carbon steel just show a small value which is for tensile strength, the total deformation and elastic strain of GRE has 3% longer than carbon steel with von mises stress of GRE just 0.003% behind the carbon steel. However, the fatigue behaviour analysis result shows that for minimum and medium geometry shows GRE has low cycle 1% behind carbon steel while for maximum geometry shows no difference for both pipes. Therefore, the GRE and carbon steel have their own strength which mean it depends on the application or situation whether to choose the GRE or carbon steel as the pipe material and GRE can be an alternative to carbon steel to use for oil and gas industry pipe. Some suggestion for future is the outcomes from this research can be validated by doing an experimental for the tensile strength, fatigue behaviour and corrosion behaviour on GRE pipes.